Geographical distribution and associated environments characterisation of catuba (Trichilia catigua A. Juss. - Meliaceae) in Paraná State - Brazil - Correa, C. [UNESP]; Ming, Lin Chau [UNESP] (My University, 2002)
Trichilia catigua A. Juss. - Meliaceae has been traditionally used as a tonic and digestive medicine. Some Brazilian pharmaceutical firms use this species to produce phytopharmaceuticals and alcoholic beverages. The aim of this work is to determine its geographical distribution and characterise the environments where catuaba is found in the state of Paraná, in order to support the domestication strategy for the agricultural production of this species. Based on the literature, botanical collections and field observations it was established, that five species of the genus occurring in Paraná, which were identified as T casaretti, T catigua, T claussenii, T elegans, T pallida and another supposed to be T pattens. Trichilia catigua occurs within a wide but defined strip in the state. By evaluating data of climate; soil types; natural vegetation formations; mean, maximum and minimum temperatures; relative humidity; rainfall; altitudes and evapotranspiration the strip may be localised above latitude 25° in the central and Eastern regions of the state and above latitude 26° in South-western Parana. In general, T catigua was found to occur on fertile, organic-matter-rich soils and predominantly under forest canopies.
Keywords: Ecology; Ethnobotany; Plant conservation; Plant domestication; Plant introduction; Vegetation